2012
DOI: 10.1371/journal.pone.0045397
|View full text |Cite|
|
Sign up to set email alerts
|

Accumulation of Pharmaceuticals, Enterococcus, and Resistance Genes in Soils Irrigated with Wastewater for Zero to 100 Years in Central Mexico

Abstract: Irrigation with wastewater releases pharmaceuticals, pathogenic bacteria, and resistance genes, but little is known about the accumulation of these contaminants in the environment when wastewater is applied for decades. We sampled a chronosequence of soils that were variously irrigated with wastewater from zero up to 100 years in the Mezquital Valley, Mexico, and investigated the accumulation of ciprofloxacin, enrofloxacin, sulfamethoxazole, trimethoprim, clarithromycin, carbamazepine, bezafibrate, naproxen, d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
102
1
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 119 publications
(118 citation statements)
references
References 72 publications
10
102
1
2
Order By: Relevance
“…As for MLs, much lower concentration and detection frequency than SAs in the urban soil was observed, and ROX was detected with maximum detection frequency of 26 % and average concentration of 0.06 μg kg −1 dw. The concentrations of SMX and ROX in our study were higher than those in the agriculture soil after long-term wastewater irrigation in Paris (Tamtam et al 2011) and in the agriculture soil fertilized with poultry or cattle manure (Karcı and Balcıoğlu 2009), but lower than the SMX concentration of 4 μg kg −1 determined in peri-urban agricultural soil after approximately 20 years irrigation with untreated wastewater in Mexico City (Dalkmann et al 2012). In contrast, (Ostermann et al 2014) have found a maximum SMZ concentration of 110 μg kg −1 in peri-urban agricultural soil from Beijing, while SMZ was only detected with the maximum concentration of 2.8 μg kg −1 in urban soil from Beijing and Shanghai in our study.…”
Section: Resultscontrasting
confidence: 70%
See 2 more Smart Citations
“…As for MLs, much lower concentration and detection frequency than SAs in the urban soil was observed, and ROX was detected with maximum detection frequency of 26 % and average concentration of 0.06 μg kg −1 dw. The concentrations of SMX and ROX in our study were higher than those in the agriculture soil after long-term wastewater irrigation in Paris (Tamtam et al 2011) and in the agriculture soil fertilized with poultry or cattle manure (Karcı and Balcıoğlu 2009), but lower than the SMX concentration of 4 μg kg −1 determined in peri-urban agricultural soil after approximately 20 years irrigation with untreated wastewater in Mexico City (Dalkmann et al 2012). In contrast, (Ostermann et al 2014) have found a maximum SMZ concentration of 110 μg kg −1 in peri-urban agricultural soil from Beijing, while SMZ was only detected with the maximum concentration of 2.8 μg kg −1 in urban soil from Beijing and Shanghai in our study.…”
Section: Resultscontrasting
confidence: 70%
“…NOR revealed the highest average concentration of 94.6 μg kg −1 (dry weight, dw), which was followed by OFL and CIP with the average concentrations of 36.6 and 9.44 μg kg −1 dw, respectively. These concentrations were lower than those in the sludge-treated soil in Switzerland (Golet et al 2002), but higher than those detected at organic vegetable bases and suburban areas in Tianjin, China (Hu et al 2010), as well as higher than those in peri-urban agricultural soil after longterm wastewater irrigation in Tianjin, China , Paris (Tamtam et al 2011), and Mexico City (Dalkmann et al 2012). In addition, Ostermann et al (2014) have detected the maximum ENR concentration of 63 μg kg −1 in peri-urban agricultural soil from Beijing, which was also lower than that of 128 μg kg −1 in our study.…”
Section: Resultsmentioning
confidence: 63%
See 1 more Smart Citation
“…The fate and effect of these compounds in soils will depend on several key factors, which go far behind the chemical properties of each one or of the soil characteristics. Compounds with low mobility, such as the antimicrobials ciprofloxacin, sulfamethoxazole, and carbamazepine, were shown to accumulate in soils with the irrigation period (0-100 years), in contrast with others highly mobile (diclofenac, naproxen, bezafibrate) (Chefetz et al, 2008;Dalkmann et al, 2012;Gibson et al, 2010;Kinney et al, 2006).…”
Section: Contaminantsmentioning
confidence: 99%
“…Although it is still very difficult to predict what may be the effect of the naked DNA in the soil, it was possible to demonstrate that antibiotic resistance genes (from both intra-and extracellular DNA) could be detected in soil in high doses by quantitative PCR after 16 months of environmental exposure (Hong et al, 2013;Selvam et al, 2012). These arguments show that even if immediate impacts are not observed, long term effects of accumulation of resistant bacteria, resistance genes and antibiotic residues should not be ignored (Dalkmann et al, 2012).…”
Section: Risks and Precautions Associated With Antibiotic Resistancementioning
confidence: 99%